Arterial elasticity, endothelial function and intracranial vascular health: A multimodal MRI study - Liu, Wenjin; Chen, Zhensen; Ortega, Dakota; Liu, Xuebing; Huang, Xiaoqin; Wang, Lulu; Chen, Li; Sun, Jie; Hatsukami, Thomas S; Yuan, Chun; Li, Haige; Yang, Junwei (Journal of cerebral blood flow and metabolism, 2021)
Vascular dysfunctions, including arterial stiffness and endothelial dysfunction, are prevalent in hypertensive subjects. We aimed to study their relations to subclinical intracranial vascular health in this study. A total of 200 older hypertensive males without overt cardiovascular or cerebrovascular diseases were recruited. Arterial elasticity was measured as carotid-femoral pulse wave velocity (cfPWV) and endothelial function was measured as digital reactive hyperemia index (RHI). Cerebrovascular health was evaluated using MRI in four aspects: intracranial atherosclerosis, brain perfusion as cerebral blood flow (CBF), vascular rarefaction analyzed as visible arterial branches on angiography using a custom-developed analysis technique and small vessel disease measured as white matter hyperintensity (WMH). There was a significant negative association between cfPWV and CBF, suggesting a link between arterial stiffness and CBF decline. Higher cfPWV was also associated with presence of intracranial stenotic plaque and greater WMH volume. RHI was positively related to CBF, indicating that endothelial dysfunction was associated with reduced CBF. All the associations remained significant after adjustment for confounding variables. Arterial stiffness and endothelial dysfunction are associated with reduced brain perfusion in older hypertensive males. Arterial stiffness is also associated with global cerebral vascular injury, affecting both small and medium-to-large arteries.